Within-Person Expectancy Theory Predictions of Accounting Students' Motivation to Achieve Academic Success. - Harrell, Adrian; Caldwell, Charles; Doty, Edwin (The Accounting Review, 1985)
Abstract ABSTRACT: This paper presents evidence to support the proposal that the force model of expectancy theory [Vroom, 1964] provides a useful conceptual framework for understanding a student's motivation to strive for academic success. Previous research examining this issue has employed the methodologically-flawed across-persons approach. Using the within-persons decision modeling approach [Stahl and Harrell, 1981], the study results indicate: (1) force model predictions of student motivation are very accurate (R =0.85); (2) increases in the value of expectancy result in declining marginal increases in a student's motivation; and (3) a student's motivation to strive for academic success is positively correlated with the student's actual behavior (academic performance). The results have implications for the grading and other policies of accounting educators who seek to establish a learning environment which fosters high student motivation.